1981
DOI: 10.1136/gut.22.7.571
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of appropriate laboratory measurements to supplement the Crohn's disease activity index.

Abstract: SUMMARYThe ability of 11 laboratory parameters to reflect the degree of activity of Crohn's disease, using a clinical index as reference point was compared by means of multiple stepwise regression analysis. Activity was best defined in decreasing order by orosomucoid, sedimentation rate, C reactive protein, alpha-l-antitrypsin, albumin, haematocrit, IgM, circulating immune complexes, serum iron, IgG, and IgA. The haematocrit, the only laboratory measurement in the Crohn's disease activity index developed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(51 citation statements)
references
References 7 publications
1
49
1
Order By: Relevance
“…T hese observat ions need co be confirmed, and considered before incorporatmg any of the laboratory indices co a practical clinical index of C ro hn's disease activ ity as hns heen suggested (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T hese observat ions need co be confirmed, and considered before incorporatmg any of the laboratory indices co a practical clinical index of C ro hn's disease activ ity as hns heen suggested (30).…”
Section: Discussionmentioning
confidence: 99%
“…However , both arc co nsidered co be relatively unsa tisfa ctory because they depend o n many subjecti ve cri teri a PEL T Ef. :lt\N et al (30). The authors' main criticism of the~c indices is thei r heavy reliance on Lhe number o f bowel movements without co nsideratio n fo r the presence o r extent of previo us intestinal resect io ns.…”
Section: Materials and Met Hodsmentioning
confidence: 99%
“…Many studies have demonstrated elevated CRP levels in patients with active CD [6][7][8][9]. It was suggested that CRP may better reflect the surface of active mucosal inflammation in CD than in ulcerative colitis [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that CRP may better reflect the surface of active mucosal inflammation in CD than in ulcerative colitis [7][8][9][10][11]. However, a recently published study denied any correlation between CRP level and endoscopically assessed mucosal status in CD patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Routine laboratory and inflammatory marker assessments as well as faecal calprotectin measurement should be conducted in all patients to establish a baseline value for future comparison [36,37,38,39,40,41,42,43,44,45,46] (level D).…”
Section: Assessment At Diagnosismentioning
confidence: 99%